2012
DOI: 10.1593/tlo.12310
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of ERα and ErbB2 Status in Cell Lines and Circulating Tumor Cells of Metastatic Breast Cancer Patients

Abstract: Hormone therapy and anti-ErbB2 therapies are prescribed according to the hormone receptor [estrogen receptor α (ERα)/progesterone receptor] and ErbB2 status of the initial tumor, but it appears that circulating tumor cells (CTCs) and, consequently, the metastatic cells may have a different receptor status. As an attempt to meet the crucial need for identification of the subpopulation of patients that will benefit from more individualized therapies, rapidly evolving therapies should allow a profiling of the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 47 publications
1
21
0
4
Order By: Relevance
“…These challenges had to be taken into consideration: the complications of nuclei permeabilization for antibody delivery, low level of ER presence, difficulties in unequivocal identification of CTCs in case of CD45+/K+ cells presence. A recent study by Bock and colleagues showed a higher percentage of ER-negative CTCs, however, the sample size of CTC positive metastatic breast cancer patients was relatively low (n = 5) [48]. In the study of Nadal et al , in contrast to our study, only non-metastatic breast cancer patients before any systemic treatment were enrolled and volume of 30 ml blood per patient was analyzed.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These challenges had to be taken into consideration: the complications of nuclei permeabilization for antibody delivery, low level of ER presence, difficulties in unequivocal identification of CTCs in case of CD45+/K+ cells presence. A recent study by Bock and colleagues showed a higher percentage of ER-negative CTCs, however, the sample size of CTC positive metastatic breast cancer patients was relatively low (n = 5) [48]. In the study of Nadal et al , in contrast to our study, only non-metastatic breast cancer patients before any systemic treatment were enrolled and volume of 30 ml blood per patient was analyzed.…”
Section: Discussionmentioning
confidence: 66%
“…This might be explained by the low correlation of mRNA and protein expression of ER [46]. To our knowledge, only two studies have been performed in which the authors have stained ER on single CTCs using ICC [47], [48]. Limited number of studies, based on ICC for the investigation of CTCs, might be explained by the technical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…We previously used various human carcinoma cell lines to develop a simple and efficient triple fluorescence technique for CTC receptor analysis, e.g., ER, HER2 [15], N -cadherin, and CD133 [26]. We tested the VDR expression in nine BC cell lines and CTCs from 23 archived metastatic BC cases.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs detected in BC patients are significantly associated with a poor outcome in both early and metastatic tumors [15,16,17,18,19]. In metastatic patients, several tumor lesions may potentially release CTCs which therefore comprehensively reflect tumor and metastasis characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Cette différence phénotypique a également été décrite pour les récepteurs hormonaux. Dans une étude, seulement 14 % des patientes avec une tumeur RH+ avaient des DTCs négatifs pour les RH [14,51,52].…”
Section: Utilisation Des Ctcs Pour La Personnalisation Des Traitementunclassified